2002
DOI: 10.1046/j.1471-4159.2003.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐Tat protein induces oxidative and inflammatory pathways in brain endothelium

Abstract: Impaired function of the brain vasculature might contribute to the development of HIV-associated dementia. For example, injury or dysfunction of brain microvascular endothelial cells (BMEC) can lead to the breakdown of the blood-brain barrier (BBB) and thus allow accelerated entry of the HIV-1 virus into the CNS. Mechanisms of injury to BMEC during HIV-1 infection are not fully understood, but the viral gene product Tat may be, at least in part, responsible for this effect. Tat can be released from infected pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(174 citation statements)
references
References 58 publications
10
162
2
Order By: Relevance
“…Here, we show that NF-B is activated in ECs following extracellular interaction of Tat with ␣ v ␤ 3 and the consequent activation of FAK, RhoA and pp60 src . In ECs, NF-B activation by Tat has, to date, been connected to the overexpression of surface adhesive molecules and/or activation of inflammatory pathways (Cooper et al, 1996;Cota-Gomez et al, 2002;Pieper et al, 2002;Toborek et al, 2003). The data here reported implicate NF-B in the motogenic activity exerted by Tat in vitro, suggesting its involvement also in the neovascularization induced by Tat in vivo.…”
Section: Tat/␣ V ␤ 3 Interaction Promotes Fak Activationmentioning
confidence: 50%
See 1 more Smart Citation
“…Here, we show that NF-B is activated in ECs following extracellular interaction of Tat with ␣ v ␤ 3 and the consequent activation of FAK, RhoA and pp60 src . In ECs, NF-B activation by Tat has, to date, been connected to the overexpression of surface adhesive molecules and/or activation of inflammatory pathways (Cooper et al, 1996;Cota-Gomez et al, 2002;Pieper et al, 2002;Toborek et al, 2003). The data here reported implicate NF-B in the motogenic activity exerted by Tat in vitro, suggesting its involvement also in the neovascularization induced by Tat in vivo.…”
Section: Tat/␣ V ␤ 3 Interaction Promotes Fak Activationmentioning
confidence: 50%
“…Tat has been shown to activate NF-B in different cell types including astrocytes (Conant et al, 1998), macrophages (Kumar et al, 1999), T-cells (Li-Weber et al, 2000) and ECs (Cooper et al, 1996;Cota-Gomez et al, 2002;Pieper et al, 2002;Toborek et al, 2003), but the mechanism(s) of activation are not fully elucidated. Indeed, Tat can induce NF-B activation both when administered extracellularly (Cota-Gomez et al, 2002) and when produced endogenously…”
Section: Tat/␣ V ␤ 3 Interaction Promotes Fak Activationmentioning
confidence: 99%
“…For example, disruption of the bloodbrain barrier is widely believed to be the main route by which HIV enters the CNS. The Tat protein, which is released from HIV-infected cells, alters vascular inflammatory responses as well as blood-brain barrier structure and function both in vitro and in vivo (Andras et al, 2003;Toborek et al, 2003). Exposure of primary cultures of brain microvascular endothelial cells (BMEC) to Tat(1-72) for 24 hours results in a decrease of claudin-1, claudin-5 and ZO-2 expression, whereas total levels of occludin and ZO-1 remained unchanged.…”
Section: Claudin Genes and Claudin Gene Expressionmentioning
confidence: 99%
“…It is well accepted that both chemokines and their receptors play a key role in HIV infection and progression. In addition, studies have shown that chemokines and their receptors are involved in the neuropathogenesis of HIV-1 infection in the CNS (Rappaport et al, 1999;Petito et al, 1999;McManus et al, 2000;Wesselingh and Thompson, 2001;Toborek et al, 2003). Chemokine receptors are important HIV-1 co-receptors, in combination with the T lymphocyte receptor, CD4.…”
Section: Introductionmentioning
confidence: 99%